THE VALUES OF MINANGKABAU CHARACTER EDUCATION IN LEARNING CIVIC EDUCATION - Akmal Akmal (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Studies on civic education learning materials about, especially the topics which are related to the rights and obligations of citizens, democracy, human rights, national identity, and national perception is very strong with the values of the Minangkabau culture imbued by the teachings of Islam which pretty much contains the values of the nation's character. Course material covering the fields of: Introduction to Civic education, National Identity, and the State Constitution, State Relations and citizens, Democracy, Rule of Law and Human Rights association, National Insights as geopolitical Indonesia, National Defence of Indonesia, National Integration, and National Strategy in state affair, including how to overcome development issues at the local, national, regional, and international level, contained a variety of Minangkabau traditional value as a contributor to educational values of the nation's character. That is what needs to be understood, and further explored, and to be finally implemented and communicated to the students in the learning process. Thus, the lecturers of civic education may play a role in planting values education on local based. The method used is a qualitative descriptive study. The objects are the 100 students who take the citizenship course as the general course at State University of Padang (UNP) during the semester of January- June 2014. The purposes of the study are: (1) to describe the values of traditional Minangkabau in strengthening civic education, (2) to find the Minangkabau traditional values tendency ​​in shaping the national character of the student based on the students’point of view. Keywords: character education, Minangkabau, Citizenship learning, and student